EKSPLORASI ORIENTASI BUDAYA INDONESIA DALAM WACANA JURNALISTIK BERBAHASA INDONESIA - Nur Fajar Arief (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to describe the Indonesian society’s cultural orientation in the microaspects of news journalistic discourses. This was an interpretive discourse analysis study. The data were analyzed using two models, namely descriptive discourse analysis and critical discourse analysis. The findings are as follows. First, the Indonesian society’s cultural orientation leads to the typology of collective culture. Second, the Indonesian society’s activities in a variety of social facts show relevance to the indicators of the position of collective culture awareness. Third, the Indonesian cultural orientations include those to: (a)loose and time-free events, (b) holistic thinking, (c) non-critical matters by accepting life as it is, (d) the human relationship with a characteristic of maintaining relation, (e) a certain status, position, and social role more than to achievement and capability, and (f) hidden vulnerability by not revealing a mistake, failure, and weakness openly and publicly